Prussian blue sodium ion battery positive electrode material and preparation method and application thereof

The surface of Prussian blue analogs is coated with conductive carbon materials through co-precipitation method and spray drying technology, which solves the problems of low conductivity and poor thermal stability of the positive electrode materials of Prussian blue sodium ion battery, and improves electrochemical performance and cyclic stability , reducing safety risks.

CN119208593AActive Publication Date: 2024-12-27SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310764133.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2024-12-27
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

The positive electrode material of Prussian blue sodium ion battery has low electrical conductivity and poor thermal stability. It is prone to defects in vacancy and coordination water structure during synthesis, resulting in a decrease in material capacity and a decrease in circulation performance, which poses safety hazards.

Method used

The Prussian blue analog was prepared by co-precipitation method, and the surface was coated with a layer of conductive carbon material. The crystallization water was removed by spray drying, and the reaction system complexing agent and temperature were regulated to reduce vacancy and improve the conductivity and cyclic stability of the material.

Benefits of technology

It improves the electrochemical performance of the positive electrode material of Prussian blue sodium ion battery, enhances the conductivity and cycling stability, solves the problem of electrolyte damage caused by coordination water, and reduces safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208593A_ABST
    Figure CN119208593A_ABST
Patent Text Reader

Abstract

The invention relates to a Prussian blue sodium-ion battery positive electrode material as well as a preparation method and application thereof. The Prussian blue sodium ion battery positive electrode material comprises a Prussian blue analogue and a conductive carbon material layer coated on the surface of the Prussian blue analogue, preferably, the component of the conductive carbon material layer is at least one of graphene, conductive graphite, carbon nanotubes and conductive carbon black.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a Prussian blue sodium ion battery positive electrode material and a preparation method and application thereof, belonging to the technical field of energy materials. Background Art

[0002] Due to the exhaustion of traditional fossil energy and the environmental pollution caused by its use, it is urgent to research and develop new clean energy. At present, new clean energy such as wind energy, solar energy, tidal energy, etc. has been vigorously developed and has occupied a certain energy market. However, due to its intermittent disadvantages, these new clean energy are subject to certain usage restrictions in time and space and cannot effectively play their due role. For this reason, it is necessary to study large-scale energy storage technology that can store the energy generated in local areas first and release it when needed, so as to achieve the effect of peak shaving and valley filling of energy generation, and then realize the effective utilization of these new clean energy.

[0003] Among various energy storage methods, electrochemical energy storage is the simplest and most efficient method, and has become the mainstream of energy storage technology development. Among them, lithium-ion batteries have been widely used in mobile phones, laptops, digital cameras, power tools and other fields due to their outstanding advantages such as high energy density, high operating voltage, long cycle life, low self-discharge rate and green environmental protection. However, with the growth of the lithium-ion battery market, the shortage of lithium resources and the rise in lithium prices have brought about the problem. Therefore, it is necessary to develop a new energy storage system with abundant resources and low prices. Sodium-ion batteries are another type of energy storage battery with similar working mechanism and battery structure to lithium-ion batteries. Recently, sodium-ion batteries have received increasing attention. The abundance of sodium resources is much higher than that of lithium elements, and they are evenly distributed around the world. They are cheap and stable, and there is no development bottleneck. Since sodium is easy to obtain and cheap, and the negative electrode current collector of sodium batteries can use aluminum foil instead of copper foil like lithium batteries, sodium-ion batteries have great potential price advantages. The material cost of sodium-ion batteries has a 30%-40% reduction compared with lithium-ion batteries. As research continues to deepen, the potential advantages of sodium-ion batteries are constantly being explored, especially their excellent performance at high and low temperatures and their high safety, which have laid a good foundation for the application of sodium-ion batteries in energy storage and power fields.

[0004] The mainstream negative electrode materials for sodium-ion batteries are hard carbon and NaTi2(PO4)3. Both have been well studied and have the characteristics of long cycle and high capacity. The electrolyte of sodium-ion batteries has also been well solved. It is mainly composed of sodium salts such as NaPF6 and NaClO4 and ester solvents, and its properties are similar to those of lithium-ion battery electrolytes. Unlike the above two types, the positive electrode material is still the bottleneck of sodium-ion batteries. Among them, the widely studied sodium positive electrodes can be divided into three categories: transition metal oxides, polyanionic compounds and Prussian blue analogs. Transition metal oxides and polyanionic compounds contain fluorine and oxygen bonds in their crystal structure, which makes Na + The transmission process in the lattice is subject to large chemical binding energy, which affects the deintercalation at the positive electrode and leads to low rate performance of the material. In addition, transition metal oxides are prone to structural damage during the cycle, resulting in loose electrodes or failure, which in turn leads to a serious reduction in the cycle life of the material; polyanionic compounds generally have low specific capacity due to the huge molecular weight of the anion. The synthesis methods of both usually involve high-temperature solid-phase methods, which require huge energy consumption.

[0005] The composition of Prussian blue (PB) and its derivatives (PBAs) can be represented by the general formula AxM[M'(CN)6]y·zH2O (A represents alkali metal ions such as Li, Na, K, M and M' represent transition metals such as Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Ba, Sr, 0≤x≤2, y≤1). M and M' can be different elements or the same element, and are usually distinguished based on their valence states. Since the two transition metal elements are in different strength coordination fields of different central ions, they will exhibit different spin states. In the (100) direction, it has a diameter of about The large ion channel has a -9 ~10 -8 cm 2 s -1 The diffusion coefficient of the material is small, which can accommodate sodium ions with a larger radius and achieve faster sodium ion migration. More importantly, due to its stable and spacious three-dimensional structure, its lattice strain is almost 0 during the insertion and extraction of sodium ions. In theory, one mole of material can achieve the insertion and extraction of two moles of sodium ions, providing a high theoretical specific capacity generated by double electron transfer. Taking the typical Na2FeFe(CN)6 as an example, its theoretical specific capacity is about 170mAhg -1 , which is higher than the 100-150mAhg of typical transition metal oxide materials. -1 The specific capacity of phosphate materials is 120 mAhg -1The specific capacity is much higher. In addition, the interaction between Prussian blue materials and interstitial cations is very small, and the transition metal sites in their structure can be replaced by many other redox-active transition metal elements without destroying the lattice structure. It can be seen that Prussian blue and its derivatives are promising cathode materials for sodium ion batteries. However, Prussian blue also has the following disadvantages: 1) The conductivity of Prussian blue cathode materials is low, and due to the poor thermal stability of the material, it is difficult to carry out high-temperature carbon coating treatment; 2) During the synthesis process of Prussian blue and its derivative materials, a large number of structural defects such as vacancies and coordinated water are prone to occur, which reduces the capacity of the material and the cycle performance; 3) The coordinated water in the lattice of Prussian blue and its derivative materials may be transferred into the electrolyte, causing electrochemical decomposition, leading to the destruction of the electrolyte and even causing safety hazards. Summary of the invention

[0006] In view of the above problems, the present invention provides a Prussian blue-based sodium ion battery positive electrode material and a preparation method and application thereof.

[0007] On the one hand, the present invention provides a Prussian blue-based sodium ion battery positive electrode material, comprising: a Prussian blue analogue, and a conductive carbon material layer coated on the surface of the Prussian blue analogue; preferably, the conductive carbon material layer is composed of at least one of graphene, conductive graphite, carbon nanotubes and conductive carbon black.

[0008] Preferably, the chemical formula of the Prussian blue analogue is Na x M[Fe(CN)6] z ·wH2O, wherein M is n transition metal elements, n≥1, 0.1≤w≤4.0, 1.40≤x≤1.95, 0.90≤z≤0.98, each transition metal element is marked as y1, y2, y3...yn, and y1+y2+y3...+yn=1.

[0009] Preferably, n≥2, and when M is at least two transition metal elements, the subscript range of each transition metal element is 0.01 to 0.90, preferably 0.2 to 0.5.

[0010] Preferably, the particle size of the Prussian blue analogue is 10 to 60 μm.

[0011] Preferably, the thickness of the conductive carbon material layer is 200 nm to 2 μm.

[0012] Preferably, the conductive carbon material layer accounts for 1 to 30 wt % of the total mass of the Prussian blue-based sodium ion battery positive electrode material.

[0013] In another aspect, the present invention provides a method for preparing a Prussian blue-based sodium ion battery positive electrode material, comprising: (1) mixing a Prussian blue analog, a conductive carbon material solution and deionized water to obtain a Prussian blue analog / conductive carbon material dispersion; (2) The obtained Prussian blue analogue / conductive carbon material dispersion is spray-dried to remove water and wrap the conductive carbon material on the surface of Prussian blue to obtain the Prussian blue-based sodium ion battery positive electrode material.

[0014] Preferably, in step (1), the mixing method is ultrasonic oscillation and / or stirring; the power of the ultrasonic oscillation is 200-700 W, and the time is not more than 6 hours; the stirring time is not more than 48 hours.

[0015] Preferably, in step (1), the mass fraction of the conductive carbon material solution is 1wt% to 20wt%; The mass ratio of the conductive carbon material solution to the Prussian blue analog is (0.1-10):1; The concentration ratio of the Prussian blue analogue to deionized water is 1 g: (10-500) mL.

[0016] Preferably, the spray drying parameters include: temperature of 180-300° C.; peristaltic pump feed rate of (10-2000) mL / h.

[0017] Preferably, the preparation method of the Prussian blue analogue comprises: S1: dissolving the sodium hexacyano salt of transition metal N, sodium salt, antioxidant and surface dispersant in deionized water by stirring to obtain a transparent clear solution A; S2: dissolving the transition metal M salt and the complexing agent in deionized water by stirring to obtain a transparent clear solution B; S3: adding the transparent clear solution B dropwise into the transparent clear solution A, stirring for reaction and then aging, and then performing solid-liquid separation by centrifugation, washing and drying to obtain a Prussian blue analogue.

[0018] Preferably, in step S1: The hexacyano sodium salt of transition metal N is one of sodium ferrocyanide decahydrate, sodium manganese cyanide decahydrate, and sodium cobalt cyanide decahydrate; The concentration of the hexacyano sodium salt of transition metal N in the transparent clear solution A is 0.01 to 10 M; The stirring process is carried out in a protective atmosphere at 25-95°C; the protective gas is one of air, nitrogen and argon; the stirring speed is 200-1500rpm; The antioxidant is at least one of butylated hydroxyanisole, butylated hydroxytoluene, linolenic acid, tert-butylhydroquinone or ascorbic acid, and the concentration of the antioxidant in the transparent clear solution A is 0.001-0.1M; The sodium salt is at least one of sodium fluoride, sodium chloride, sodium bromide, sodium iodide, sodium acetate, sodium nitrate, sodium sulfate, sodium oxalate, and disodium ethylenediaminetetraacetate, and the weight ratio of the sodium salt to the transition metal M salt is (1-10):1; The surface dispersant is at least one of polyvinyl pyrrolidone, hexadecyl trimethyl ammonium bromide, polycyclic aromatic hydrocarbons, and sodium dodecyl benzene sulfonate, and the concentration of the surface dispersant in the transparent clear solution A is 0.1 g to 100 g / L. The use of the surface dispersant, on the one hand, further promotes the orderly growth of the grains and prevents the aggregation of Prussian blue during the synthesis process; on the other hand, the addition of the surface dispersant improves the distribution, regulates the overall microscopic morphology of the material, makes it reach a large size, and increases the particle size; thereby obtaining a uniform single-phase structure with high crystallinity and regular large-sized crystals.

[0019] Preferably, in step S2: The concentration of the transition metal M salt in the transparent clear solution B is 0.01 to 10 M; The complexing agent sodium salt is selected from at least one of sodium citrate, 2,2'-bipyridine, 1-10-phenanthroline, ethylenediamine, ethylenediaminetetraacetic acid, trisodium nitrilotriacetate, sodium oxalate, disodium ethylenediaminetetraacetate, sodium gluconate, sodium tartrate or sodium acetate, and the weight ratio of the complexing agent to the transition metal M salt is (1-10):1; The stirring process is carried out in a protective atmosphere at 25-95° C.; the protective gas is at least one of air, nitrogen and argon; and the stirring speed is 200-1500 rpm.

[0020] Preferably, in step S3; The dropping process is carried out at 25-95° C. in a protective atmosphere; the protective gas is at least one of air, nitrogen and argon; The dropwise addition flow rate of the transparent clear solution B is 1 mL / min to 50 mL / min; The stirring reaction temperature is 25 to 95°C and the time is 0.5 to 12 hours; The aging temperature is 25 to 95° C. and the aging time is 2 to 72 hours; The centrifugal solid-liquid separation method has a centrifugal speed of 6000-10000 rpm and a time of 5-10 minutes; The drying is vacuum drying, and the vacuum degree is 10 -6 ~10 -2pa, drying temperature is 100-220℃, and drying time is 6-24h.

[0021] On the other hand, the present invention provides a sodium ion battery, comprising: a positive electrode containing the above-mentioned Prussian blue-based sodium ion battery positive electrode material.

[0022] Beneficial effects of the present invention: 1. The present invention adopts a coprecipitation method to prepare a Prussian blue cathode material. By regulating the sodium salt of the complexing agent in the reaction system, the reaction temperature and the addition of the sodium salt, slow growth of the material crystal and less vacancies are achieved during the synthesis process. Subsequently, a spray drying method is used to remove the crystal water inside the material system to obtain a low-water-content and low-vacancy Prussian blue sodium ion battery cathode material, which solves the problem of coordinated water in conventional Prussian blue cathode materials, thereby improving the electrochemical performance of the sodium ion battery; 2. In the present invention, the method of spray drying and coating the conductive carbon material on the surface of Prussian blue is adopted to overcome the problem of poor conductivity of Prussian blue complexes, increase the conductivity of the Prussian blue positive electrode, reduce polarization, and greatly increase the cycle stability of the Prussian blue positive electrode. In particular, due to the doping of inert components in the multi-component Prussian blue, it is far superior to iron-based Prussian blue in terms of cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Figure ac is the SEM electron microscope image of the carbon-wrapped anhydrous Prussian blue type sodium ion battery positive electrode material prepared in Examples 1 to 3, and Figure d is the SEM electron microscope image of the Prussian blue type sodium ion battery positive electrode material prepared in Example 1; Figure 2 Figures ac are XRD patterns of the carbon-wrapped anhydrous Prussian blue-based sodium ion battery positive electrode materials prepared in Examples 1-3, and Figure d is the XRD pattern of the Prussian blue-based sodium ion battery positive electrode materials prepared in Comparative Example 1; Figure 3 This is a cycle performance diagram of a sodium ion half-cell of an organic electrolyte system with a Prussian blue material as a positive electrode prepared in Example 1 at a current density of 500 mA / g; Figure 4 This is a cycle performance diagram of a sodium ion half-cell of an organic electrolyte system with a Prussian blue material as a positive electrode prepared in Example 2 at a current density of 500 mA / g; Figure 5 This is a cycle performance diagram of a sodium ion half-cell of an organic electrolyte system with a Prussian blue material as a positive electrode prepared in Example 3 at a current density of 500 mA / g; Figure 6This is a cycle performance diagram of a sodium ion half-cell of an organic electrolyte system with a Prussian blue material as a positive electrode prepared in Example 4 at a current density of 500 mA / g; Figure 7 This is a cycle performance diagram of a sodium ion half-cell of an organic electrolyte system with a Prussian blue material as a positive electrode prepared in Comparative Example 1 at a current density of 500 mA / g; Figure 8 This is a graph showing the cycling performance of a sodium ion half-cell of an organic electrolyte system using a Prussian blue material as a positive electrode prepared in Comparative Example 2 at a current density of 500 mA / g. DETAILED DESCRIPTION

[0024] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0025] In the present disclosure, a coprecipitation method is used to prepare a Prussian blue cathode material, and by regulating the sodium salt of the complexing agent in the reaction system and the reaction temperature, the slow growth of the material crystal is achieved, and the generation of vacancies is reduced. Then, by a spray drying method, while removing the crystal water inside the material system, a low-water-content, low-vacancy Prussian blue sodium ion battery cathode material is obtained, and a layer of conductive carbon material (preferably graphene) is wrapped on the surface of the Prussian blue, which solves the problem of coordinated water in conventional Prussian blue cathode materials, alleviates the problem of low conductivity of Prussian blue cathode materials, and improves the electrochemical performance of sodium ion batteries.

[0026] In the present invention, a multi-component Prussian blue is used, and a more stable Prussian blue-based sodium ion battery positive electrode material is formed by the method of early inert element doping and later synthesis. The preparation method of the Prussian blue-based sodium ion battery positive electrode material is exemplified below.

[0027] Under a certain temperature and protective atmosphere, soluble sodium hexacyano salt of transition metal N, sodium salt, antioxidant, and surface dispersant are dissolved in deionized water, and after stirring, a transparent clear solution A is obtained. The certain temperature range is 25-95° C.; the protective gas is one or more of air, nitrogen, and argon; and the stirring speed is 200-1500 rpm.

[0028] In an optional embodiment, the hexacyano sodium salt of transition metal N is one of sodium ferrocyanide decahydrate, sodium manganese cyanide decahydrate, or sodium cobalt cyanide decahydrate. The concentration of the soluble hexacyano sodium salt of transition metal N in solution A is 0.01 to 10M. The concentration of the antioxidant in solution B is 0.001 to 0.1M; the weight ratio of the sodium salt to the transition metal M salt is (1 to 10): 1; the concentration of the surface dispersant in solution B is 0.1g to 100g / L. The sodium salt of the complexing agent is selected from at least one of sodium citrate, 2,2'bipyridine, 1 10-phenanthroline, ethylenediamine, ethylenediaminetetraacetic acid, trisodium nitrilotriacetate, sodium oxalate, disodium ethylenediaminetetraacetate, sodium gluconate, sodium tartrate, or sodium acetate. The antioxidant is at least one of butylated hydroxyanisole, dibutylhydroxytoluene, linolenic acid, tert-butylhydroquinone, or ascorbic acid. The sodium salt is at least one of sodium fluoride, sodium chloride, sodium bromide, sodium iodide, sodium acetate, sodium nitrate, sodium sulfate, sodium oxalate, and disodium ethylenediaminetetraacetate. The surface dispersant is at least one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, polycyclic aromatic hydrocarbons, and sodium dodecylbenzene sulfonate.

[0029] Under a certain temperature and protective atmosphere, a soluble transition metal M salt and a complexing agent are dissolved in deionized water to obtain a transparent clear solution B. The certain temperature range is 25 to 95° C.; the protective gas is one or more of air, nitrogen, and argon.

[0030] In an optional embodiment, the concentration of the soluble transition metal M salt in solution B is 0.01-10 M; the weight ratio of the complexing agent to the transition metal M salt is (1-10):1.

[0031] At a certain temperature and protective atmosphere, solution B is slowly added dropwise to solution A, stirred for reaction, and then aged, and finally solid-liquid separation, washing, and drying are performed by centrifugation to obtain the Prussian blue analog to be treated. The certain temperature range is 25 to 95°C; the protective gas is one or more of air, nitrogen, and argon.

[0032] In an optional embodiment, the flow rate of solution B when added dropwise to solution A is 1 mL / min to 50 mL / min. The centrifugal speed of the centrifugal solid-liquid separation method is 6000 to 10000 rpm, and the time is 5 to 10 minutes. The drying is vacuum drying, and the vacuum degree is 10 -6 ~10 -2 pa, drying temperature is 100-220℃, and drying time is 6-24h.

[0033] The composite slurry of the Prussian blue analogue and the conductive carbon material to be treated is added to water and fully dispersed by ultrasonic oscillation / stirring to obtain a Prussian blue analogue / conductive carbon material dispersion liquid, wherein the ultrasonic oscillation time is 0 to 6 hours and the stirring time is 0 to 48 hours.

[0034] In an optional embodiment, the mass fraction of the conductive carbon material composite slurry is 1wt% to 10wt%. The mass ratio of the conductive carbon material composite slurry to the Prussian blue analog to be treated is (0.1 to 10) g / g. The concentration ratio of the Prussian blue analog to be treated to water is 1 g / (10 to 500) mL.

[0035] The Prussian blue analogue / conductive carbon material dispersion is spray dried to obtain a low-water content conductive carbon material wrapped with a Prussian blue type sodium ion battery positive electrode material. The spray drying temperature is 180-300°C; the peristaltic pump feed rate during spray drying is (10-2000) mL / h.

[0036] In the present invention, the Prussian blue-based sodium ion battery positive electrode material can be used as the sodium ion battery positive electrode, which can effectively improve the electrochemical performance of the sodium ion battery.

[0037] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0038] Embodiment 1: 2 mol of sodium ferrocyanide decahydrate, 10 g of polyvinyl pyrrolidone, 1 g of ascorbic acid, and 1 mol of sodium chloride were dissolved in 1 L of deionized water to form a precursor solution A; 1.5 mol of manganese sulfate, 0.5 mol of copper sulfate, and 5 mol of sodium citrate were dissolved in 1 L of deionized water to obtain a precursor solution B; a peristaltic pump was used to slowly drop the precursor solution B into the container A through a silicone tube at a rate of 10 mL / min, the reaction temperature was room temperature, and the stirring rate was 400 rpm. After the precursor B was added dropwise, it was stirred continuously at room temperature for 8 hours and then allowed to stand for 40 hours to obtain a sample suspension; the sample suspension was centrifuged at 6000 rpm for 10 minutes, and the obtained sample precipitate was washed with deionized water and ethanol for multiple times, and the product was placed in a vacuum oven at a temperature of 160°C and a vacuum degree of 1 pa and dried for 10 hours, thereby obtaining a Prussian blue analog.

[0039] 40 g of a Prussian blue analog and 20 g of a 20 wt% graphene composite slurry were added to 1 L of deionized water, and ultrasonically vibrated for 2 h and then vigorously stirred for 2 h. During the spray drying process, the peristaltic pump feed rate was 200 mL / h and the drying temperature was selected to be 250 °C to obtain carbon-encapsulated anhydrous Prussian blue.

[0040] The chemical formula of the material was determined to be Na by inductively coupled plasma optical emission spectroscopy (ICP-OES), CHN elemental analysis, and thermogravimetric analysis. 1.72 Mn 0.75 Cu 0.25 [Fe(CN)6] 0.97 □ 0.03 0.15H2O@0.1C (□ means vacancy, 0.1 means 10wt%).

[0041] Through SEM test analysis, it can be seen that the carbon-wrapped Prussian blue sodium ion battery positive electrode material prepared in this embodiment presents a spherical polyhedral morphology, and the average length of a single crystal is 40 μm. Figure 1 As shown in (a).

[0042] XRD test analysis shows that the carbon-wrapped Prussian blue-based sodium-ion battery positive electrode material has high crystallinity. Figure 2 As shown in (a).

[0043] The carbon-wrapped Lushi blue-based sodium ion battery positive electrode material prepared in Example 1 was assembled into a sodium ion half-cell, and its cycle performance was tested. Figure 3 As shown, the maximum discharge capacity of the material at a current density of 500 mA / g is 108.5 mAh / g, and the specific capacity retention rate of the battery after 500 cycles is 92.44%, showing excellent cycle performance.

[0044] Embodiment 2: 3 mol of sodium ferrocyanide decahydrate, 5 g of sodium dodecylbenzene sulfonate, 2 g of butylated hydroxyanisole, and 2 mol of sodium bromide were dissolved in 2 L of deionized water to form a precursor solution A; 0.4 mol of manganese acetate, 0.4 mol of copper acetate, 0.4 mol of cobalt acetate, 0.4 mol of zinc acetate, 0.4 mol of iron acetate, and 10 mol of sodium oxalate were dissolved in 2 L of deionized water to obtain a precursor solution B; a peristaltic pump was used to slowly drop the precursor solution B into the container A through a silicone tube at a rate of 50 mL / min, the reaction temperature was room temperature, and the stirring rate was 600 rpm. After the precursor B was added dropwise, it was stirred continuously at room temperature for 6 hours and then allowed to stand for 66 hours to obtain a sample suspension; the sample suspension was centrifuged at 8000 rpm for 5 minutes, the obtained sample precipitate was washed with deionized water and ethanol for multiple times, and the product was placed in a vacuum oven at a temperature of 200 ° C and a vacuum degree of 10 Pa and dried for 12 hours to obtain a Prussian blue analogue; 40 g of a Prussian blue analog and 60 g of a 10 wt% graphene composite slurry were added to 2 L of deionized water, and ultrasonically vibrated for 4 h and then vigorously stirred for 2 h. During the spray drying process, the peristaltic pump feed rate was 400 mL / h and the drying temperature was selected to be 280 °C to obtain carbon-encapsulated anhydrous Prussian blue.

[0045] The chemical formula of the material was determined to be Na by inductively coupled plasma optical emission spectroscopy (ICP-OES), CHN elemental analysis, and thermogravimetric analysis. 1.56 Mn 0.2 Fe 0.2 Co 0.2 Zn 0.2 Cu 0.2 [Fe(CN)6] 0.96 □ 0.04 0.11H2O@0.15C (□ means vacancy, 0.15 means 15wt%).

[0046] Through SEM test analysis, it can be seen that the carbon-wrapped Prussian blue sodium ion battery positive electrode material prepared in this embodiment presents a spherical polyhedron morphology, and the average length of a single crystal is 30 μm. Figure 1 As shown in (b).

[0047] XRD test analysis shows that the carbon-wrapped Prussian blue-based sodium-ion battery positive electrode material has high crystallinity. Figure 2 As shown in (b).

[0048] The carbon-wrapped Lushi blue-based sodium ion battery positive electrode material prepared in Example 2 was assembled into a sodium ion half-cell, and its cycle performance was tested. Figure 4As shown, the maximum discharge capacity of the material at a current density of 500 mA / g is 90.1 mAh / g, and the specific capacity retention rate of the battery after 500 cycles is 94.89%, showing excellent cycle performance.

[0049] Embodiment 3: 6 mol of sodium ferrocyanide decahydrate, 8 g of hexadecyltrimethylammonium bromide, 0.5 g of linolenic acid, and 5 mol of sodium sulfate were dissolved in 1 L of deionized water to form a precursor solution A; 2 mol of ferric chloride, 2 mol of cobalt chloride, 2 mol of nickel chloride, and 20 mol of sodium oxalate were dissolved in 2 L of deionized water to obtain a precursor solution B; a peristaltic pump was used to slowly drop the precursor solution B into the container A through a silicone tube at a rate of 20 mL / min, the reaction temperature was room temperature, and the stirring rate was 800 rpm. After the precursor B was added dropwise, it was stirred continuously at room temperature for 12 hours and then allowed to stand for 36 hours to obtain a sample suspension; the sample suspension was centrifuged at 10000 rpm for 5 minutes, and the obtained sample precipitate was washed with deionized water and ethanol for multiple times, and the product was placed in a vacuum oven at a temperature of 180°C and a vacuum degree of 30 Pa and dried for 12 hours, thereby obtaining a Prussian blue analog. 30 g of Prussian blue analogue and 60 g of 5 wt% graphene composite slurry were put into 1 L of deionized water, ultrasonically vibrated for 0.5 h and then vigorously stirred for 4 hours. During the spray drying process, the peristaltic pump feed rate was 300 mL / h and the drying temperature was selected to be 260 ° C to obtain carbon-encapsulated anhydrous Prussian blue.

[0050] The chemical formula of the material was determined to be Na by inductively coupled plasma optical emission spectroscopy (ICP-OES), CHN elemental analysis, and thermogravimetric analysis. 1.58 Fe 0.33 Co 0.33 Ni 0.33 [Fe(CN)6] 0.92 □ 0.08 0.13H2O@0.1C (□ means vacancy, 0.1 means 10wt%).

[0051] Through SEM test analysis, it can be seen that the carbon-wrapped Prussian blue sodium ion battery positive electrode material prepared in this embodiment presents a spherical polyhedral morphology, and the average length of a single crystal is 40 μm. Figure 1 As shown in (c).

[0052] XRD test analysis shows that the carbon-wrapped Prussian blue-based sodium-ion battery positive electrode material has high crystallinity. Figure 2 As shown in (c).

[0053] The carbon-wrapped Lushi blue-based sodium ion battery positive electrode material prepared in Example 3 was assembled into a sodium ion half-cell, and its cycle performance was tested. Figure 5 As shown, the maximum discharge capacity of the material at a current density of 500 mA / g is 91.3 mAh / g, and the specific capacity retention rate of the battery after 500 cycles is 92.1%, showing excellent cycle performance.

[0054] Embodiment 4: 2 mol of sodium ferrocyanide decahydrate, 10 g of polyvinyl pyrrolidone, 1 g of ascorbic acid, and 1 mol of sodium chloride were dissolved in 1 L of deionized water to form a precursor solution A; 2 mol of ferrous acetate and 5 mol of sodium citrate were dissolved in 1 L of deionized water to obtain a precursor solution B; a peristaltic pump was used to slowly drop the precursor solution B into the container A through a silicone tube at a rate of 10 mL / min, the reaction temperature was room temperature, and the stirring rate was 400 rpm. After the precursor B was added, it was stirred continuously at room temperature for 8 hours and then allowed to stand for 40 hours to obtain a sample suspension; the sample suspension was centrifuged at 6000 rpm for 10 minutes, and the obtained sample precipitate was washed with deionized water and ethanol for multiple times, and the product was placed in a vacuum oven at a temperature of 160 ° C and a vacuum degree of 1 pa and dried for 10 hours, thereby obtaining a Prussian blue analog.

[0055] 40 g of a Prussian blue analog and 20 g of a 20 wt% graphene composite slurry were added to 1 L of deionized water, and ultrasonically vibrated for 2 h and then vigorously stirred for 2 h. During the spray drying process, the peristaltic pump feed rate was 200 mL / h and the drying temperature was selected to be 250 °C to obtain carbon-encapsulated anhydrous Prussian blue.

[0056] The chemical formula of the material was determined to be Na by inductively coupled plasma optical emission spectroscopy (ICP-OES), CHN elemental analysis, and thermogravimetric analysis. 1.95 Fe 0.95 [Fe(CN)6] 0.95 □ 0.05 0.25H2O@0.1C (□ means vacancy, 0.1 means 10wt%).

[0057] Through SEM test analysis, it can be seen that the carbon-wrapped Prussian blue sodium ion battery positive electrode material prepared in this embodiment presents a spherical polyhedral morphology, and the average length of a single crystal is 40 μm. Figure 1 As shown in (d).

[0058] XRD test analysis shows that the carbon-wrapped Prussian blue-based sodium-ion battery positive electrode material has high crystallinity. Figure 2 As shown in (d).

[0059] The carbon-wrapped Lushi blue-based sodium ion battery cathode material prepared in Example 4 was assembled into a sodium ion half-cell, and its cycle performance was tested. Figure 6 As shown, the maximum discharge capacity of the material at a current density of 500 mA / g is 112.6 mAh / g, and the specific capacity retention rate of the battery after 500 cycles is 86.32%, showing excellent cycle performance.

[0060] Comparative Example 1: In this comparative example 1, the preparation process of the Prussian blue sodium ion battery positive electrode material is referred to Example 1, except that: 2 mol of sodium ferrocyanide decahydrate, 10 g of polyvinyl pyrrolidone, 1 g of ascorbic acid, and 1 mol of sodium chloride are dissolved in 1 L of deionized water to form a precursor solution A; 1.5 mol of manganese sulfate, 0.5 mol of copper sulfate, and 5 mol of sodium citrate are dissolved in 1 L of deionized water to obtain a precursor solution B; the precursor solution B is slowly added dropwise to the container A at a rate of 10 mL / min through a silicone tube using a peristaltic pump, the reaction temperature is room temperature, and the stirring rate is 400 rpm. After the precursor B is added dropwise, stirring is continued at room temperature for 8 hours and then allowed to stand for 40 hours to obtain a sample suspension; the sample suspension is centrifuged at 6000 rpm for 10 minutes, the obtained sample precipitate is washed multiple times with deionized water and ethanol, and the product is placed in a vacuum oven at a temperature of 160° C. and a vacuum degree of 1 Pa and dried for 10 hours to obtain a Prussian blue analogue without subsequent graphene coating.

[0061] The chemical formula of the material prepared in this comparative example 1 was determined to be Na 1.72 Mn 0.75 Cu 0.25 [Fe(CN)6] 0.97 □ 0.03 ·2.15H2O.

[0062] The Prussian blue prepared in this comparative example 1 was used as the positive electrode material of a sodium ion battery to assemble a sodium ion half-cell, and its cycle performance was tested. Figure 7 As shown, the maximum discharge capacity of the material at a current density of 500 mA / g is 103.5 mAh / g, and the specific capacity retention rate of the battery after 500 cycles is 80.2%, and the cycle stability performance is poor.

[0063] Comparative Example 2: In this comparative example 2, the preparation process of the Prussian blue sodium ion battery positive electrode material is as shown in Example 4, except that: 2 mol of sodium ferrocyanide decahydrate, 10 g of polyvinyl pyrrolidone, 1 g of ascorbic acid, and 1 mol of sodium chloride are dissolved in 1 L of deionized water to form a precursor solution A; 2 mol of ferrous sulfate and 5 mol of sodium citrate are dissolved in 1 L of deionized water to obtain a precursor solution B; a peristaltic pump is used to slowly drop the precursor solution B into the container A at a rate of 10 mL / min through a silicone tube, the reaction temperature is room temperature, and the stirring rate is 400 rpm. After the precursor B is added dropwise, it is stirred continuously at room temperature for 8 hours and then allowed to stand for 40 hours to obtain a sample suspension; the sample suspension is centrifuged at 6000 rpm for 10 minutes, and the obtained sample precipitate is washed with deionized water and ethanol for multiple times, and the product is placed in a vacuum oven at a temperature of 160 ° C and a vacuum degree of 1 pa and dried for 10 hours to obtain a Prussian blue analogue without subsequent graphene coating.

[0064] The chemical formula of the material prepared in this comparative example 2 was determined to be Na 1.95 Fe[Fe(CN)6] 0.95 □ 0.05 ·2.05H2O.

[0065] The Prussian blue prepared in this comparative example 2 was used as the positive electrode material of a sodium ion battery to assemble a sodium ion half-cell, and its cycle performance was tested. Figure 8 As shown, the maximum discharge capacity of the material at a current density of 500 mA / g is 111.6 mAh / g, and the specific capacity retention rate of the battery after 500 cycles is 75.20%, and the cycle stability performance is poor.

Claims

1. A Prussian blue sodium ion battery positive electrode material, characterized in that: include: A Prussian blue analogue, and a conductive carbon material layer coated on the surface of the Prussian blue analogue; preferably, the conductive carbon material layer is composed of at least one of graphene, conductive graphite, carbon nanotubes and conductive carbon black.

2. The Prussian blue-based sodium ion battery positive electrode material according to claim 1, characterized in that: The chemical formula of the Prussian blue analog is Na x M[Fe(CN)6] z ·wH2O, wherein M is n transition metal elements, n≥1, 0.1≤w≤4.0, 1.40≤x≤1.95, 0.90≤z≤0.98, each transition metal element is marked as y1, y2, y3...yn, and y1+y2+y3...+yn=1.

3. The Prussian blue-based sodium ion battery positive electrode material according to claim 2, characterized in that: n≥2, and when M is at least two transition metal elements, the subscript range of each transition metal element is 0.01 to 0.90, preferably 0.2 to 0.

5.

4. The Prussian blue-based sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that: The particle size of the Prussian blue analogue is 10 to 60 μm.

5. The Prussian blue-based sodium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: The thickness of the conductive carbon material layer is 200 nm to 2 μm; the conductive carbon material layer accounts for 1 to 30 wt % of the total mass of the Prussian blue-based sodium ion battery positive electrode material.

6. A method for preparing a Prussian blue-based sodium ion battery positive electrode material as claimed in claim 1, characterized in that: include: (1) mixing a Prussian blue analog, a conductive carbon material composite slurry and deionized water to obtain a Prussian blue analog / conductive carbon material dispersion; (2) The obtained Prussian blue analogue / conductive carbon material dispersion is spray-dried to remove water and wrap the conductive carbon material on the surface of Prussian blue to obtain the Prussian blue-based sodium ion battery positive electrode material.

7. The preparation method according to claim 6, characterized in that: In step (1), the mixing method is ultrasonic oscillation and / or stirring; the power of the ultrasonic oscillation is 200-700W, and the time is not more than 6 hours; the stirring time is not more than 48 hours.

8. The preparation method according to claim 6, characterized in that: In step (1), the conductive carbon material composite slurry has a mass fraction of 1wt% to 20wt%; The mass ratio of the conductive carbon material solution to the Prussian blue analog is (0.1-10):1; The concentration ratio of the Prussian blue analogue to deionized water is 1 g: (10-500) mL.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The spray drying parameters include: temperature of 180-300° C.; peristaltic pump feed rate of (10-2000) mL / h.

10. The preparation method according to any one of claims 6 to 9, characterized in that: The preparation method of the Prussian blue analogue comprises: S1: dissolving the sodium hexacyano salt of transition metal N, sodium salt, antioxidant and surface dispersant in deionized water by stirring to obtain a transparent clear solution A; S2: dissolving the transition metal M salt and the complexing agent in deionized water by stirring to obtain a transparent clear solution B; S3: adding the transparent clear solution B dropwise into the transparent clear solution A, stirring for reaction and then aging, and then performing solid-liquid separation by centrifugation, washing and drying to obtain a Prussian blue analogue.

11. The preparation method according to claim 10, characterized in that: In step S1: The hexacyano sodium salt of transition metal N is one of sodium ferrocyanide decahydrate, sodium manganese cyanide decahydrate, and sodium cobalt cyanide decahydrate; The concentration of the hexacyano sodium salt of transition metal N in the transparent clear solution A is 0.01 to 10 M; The stirring process is carried out in a protective atmosphere at 25-95°C; the protective gas is one of air, nitrogen and argon; the stirring speed is 200-1500rpm; The antioxidant is at least one of butylated hydroxyanisole, butylated hydroxytoluene, linolenic acid, tert-butylhydroquinone or ascorbic acid, and the concentration of the antioxidant in the transparent clear solution A is 0.001-0.1M; The sodium salt is at least one of sodium fluoride, sodium chloride, sodium bromide, sodium iodide, sodium acetate, sodium nitrate, sodium sulfate, sodium oxalate, and disodium ethylenediaminetetraacetate, and the weight ratio of the sodium salt to the transition metal M salt is (1-10):1; The surface dispersant is at least one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, polycyclic aromatic hydrocarbons, and sodium dodecylbenzene sulfonate. The concentration of the surface dispersant in the transparent clear solution A is 0.1 g to 100 g / L.

12. The preparation method according to claim 10, characterized in that: In step S2: The concentration of the transition metal M salt in the transparent clear solution B is 0.01 to 10 M; The complexing agent sodium salt is selected from at least one of sodium citrate, 2,2'-bipyridine, 1-10-phenanthroline, ethylenediamine, ethylenediaminetetraacetic acid, trisodium nitrilotriacetate, sodium oxalate, disodium ethylenediaminetetraacetate, sodium gluconate, sodium tartrate or sodium acetate, and the weight ratio of the complexing agent to the transition metal M salt is (1-10):1; The stirring process is carried out in a protective atmosphere at 25-95° C.; the protective gas is at least one of air, nitrogen and argon; and the stirring speed is 200-1500 rpm.

13. The preparation method according to claim 10, characterized in that: In step S3; The dropping process is carried out at 25-95° C. in a protective atmosphere; the protective gas is at least one of air, nitrogen and argon; The dropwise addition rate of the transparent clear solution B is 1 mL / min to 50 mL / min; The stirring reaction temperature is 25 to 95°C and the time is 0.5 to 12 hours; The aging temperature is 25 to 95° C. and the aging time is 2 to 72 hours; The centrifugal solid-liquid separation method has a centrifugal speed of 6000-10000 rpm and a time of 5-10 minutes; The drying is vacuum drying, and the vacuum degree is 10 -6 ~10 -2 pa, drying temperature is 100-220℃, and drying time is 6-24h.

14. A sodium ion battery, characterized in that: include: A positive electrode comprising the Prussian blue-based sodium ion battery positive electrode material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Prussian blue / reduced graphene oxide composite material as well as preparation method and application thereof

    CN104716314A

  • Graphene rapidly-coated Prussian blue sodium ion battery positive electrode material and preparation method thereof

    CN108565422A

  • Low-altitude Prussian blue sodium ion battery positive electrode material and preparation method thereof

    CN110510638A

  • High-entropy Prussian blue material and preparation method thereof

    CN113690433A

  • Supergravity synthesis method and application of Prussian blue material

    CN115432718A